2020
DOI: 10.3390/molecules25051070
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Bioproduction of Itaconic and Fumaric Acids Based on Solid-State Fermentation of Lignocellulosic Biomass

Abstract: The bioproduction of high-value chemicals such as itaconic and fumaric acids (IA and FA, respectively) from renewable resources via solid-state fermentation (SSF) represents an alternative to the current bioprocesses of submerged fermentation using refined sugars. Both acids are excellent platform chemicals with a wide range of applications in different market, such as plastics, coating, or cosmetics. The use of lignocellulosic biomass instead of food resources (starch or grains) in the frame of a sustainable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…One promising sustainable feedstock is (lignocellulosic) biomass, in which polymeric sugar chains, e.g., cellulose and hemicellulose, and lignin can be converted into a great variety of chemicals [3]. This can be done either by hydrolysis [4][5][6][7], fermentation [8][9][10], or combinations thereof (enzymatic hydrolysis) [11,12]. Typical hydrolysis products [4,7,13] include formic acid, levulinic acid, and furfural, formed via sugars and 5-hydroxymethylfurfural, while products from fermentation can be acetic acid [14,15], propionic acid [14,15], butyric acid [14,15], and L-lactic acid [14][15][16], but valeric acid [17], caproic acid [17], succinic acid [16,18], itaconic acid [16], mandelic acid [16], and alcohols [15] are also known to be produced.…”
Section: Introductionmentioning
confidence: 99%
“…One promising sustainable feedstock is (lignocellulosic) biomass, in which polymeric sugar chains, e.g., cellulose and hemicellulose, and lignin can be converted into a great variety of chemicals [3]. This can be done either by hydrolysis [4][5][6][7], fermentation [8][9][10], or combinations thereof (enzymatic hydrolysis) [11,12]. Typical hydrolysis products [4,7,13] include formic acid, levulinic acid, and furfural, formed via sugars and 5-hydroxymethylfurfural, while products from fermentation can be acetic acid [14,15], propionic acid [14,15], butyric acid [14,15], and L-lactic acid [14][15][16], but valeric acid [17], caproic acid [17], succinic acid [16,18], itaconic acid [16], mandelic acid [16], and alcohols [15] are also known to be produced.…”
Section: Introductionmentioning
confidence: 99%
“…A new approach in IA production is found in solid-state fermentation (SSF), which provides numerous advantages in contrast with submerged fermentation (SmF) which is mainly used in the production of IA [ 79 ]. These advantages are provided via small-scale and simpler bioreactors (small water quantity), diminished effluent quantity, higher productivity, simpler aeration, and preferable due to better natural environment simulation [ 80 , 81 , 82 ].…”
Section: Itaconic Acid (Ia) Synthesismentioning
confidence: 99%
“…83 This would require microbial strains that are resistant to impurities in the biomass hydoxylate. Various studies have been reported that utilise lignocellulosic biomass such as sugarcane bagasse, 84 bran, 85 corn stover, 86 corn cob 87 and bamboo residues, 88 for IA production. Itaconic production from algal biomass hydrolysate and waste glycerol from biodiesel has been reported using A. niveus, resulting in a final titre of 31.5 g L −1 .…”
Section: Lactic Acidmentioning
confidence: 99%